“Can my mother come?” Asylum interviews with unaccompanied and separated children seeking asylum in the Netherlands - Rap, Stephanie E. (Frontiers in Human Dynamics, 2023)
The UN Convention on the Rights of the Child (CRC) accords children the right to give their views on all important decisions in their life (art. 12 CRC). In the past decades increased awareness has risen among professionals who work with children in judicial and administrative proceedings, to hear their voices. The key question guiding this research was whether refugee children have the possibility to meaningfully participate in asylum proceedings, as required by international children’s rights law and standards? Asylum application procedures are highly complex administrative procedures, that are often not adapted to the capacities and level of maturity of children. Recent studies suggest that the right to participation and information is insufficiently safeguarded for children involved in asylum procedures. Unaccompanied children seeking asylum as young as six years of age have to go through the asylum procedure in the Netherlands. Efforts have been put in making this procedure more child-friendly, by designing a child-friendly interview room and training immigration officers. The aim of this study was to explore to what extent the immigration authority takes into account children’s voice, age and development, in line with international children’s rights. Observations have been conducted of asylum interviews with children aged 7 to 11. The results show that child-friendly conversation techniques and tools are used to some extent, however, immigration officers should be trained more extensively in order to enhance the effective participation of young children. It is concluded that interviews with children could be improved by giving children more information and using techniques to communicate with young children.